Characterization of a novel type homoserine dehydrogenase with high oxidation activity from Arthrobacter nicotinovorans. (March 2022) - Liang, Xinxin; Deng, Huaxiang; Bai, Yajun; Fan, Tai-Ping; Zheng, Xiaohui; Cai, Yujie
Graphical abstract: Highlights: A novel homoserine dehydrogenase ( An HSD) from A. nicotinovorans was identified. An HSD was not homologous to HSDs enzymes which are part of the aspartate pathway. An HSD was insensitive to the feedback inhibition of l -threonine and l -methionine. This study provided possibility for the biosynthesis of l -aspartate-β-semialdehyde. Abstract: Homoserine dehydrogenase (HSD) is a key enzyme in the synthesis pathway of the aspartate family of amino acids. HSD can catalyze the reversible reaction of l -aspartate-β-semialdehyde (l -Asa) to l -homoserine (l -Hse). In this study, one putative homoserine dehydrogenase from Arthrobacter nicotinovorans, which was named An HSD, was different from those HSDs that from the aspartic acid metabolic pathway, and might be responsible for the specific oxidation of l -Hse. Surprisingly, the analysis showed that the purified An HSD exhibited high oxidation activity of l -Hse. At pH 10.0 and 40 °C, the Km and kcat of An HSD was 5.97 ± 1.10 mM and 3.61 s −1, respectively. In terms of cofactor reliance, An HSD preferred NAD + than NADP + as a cofactor. The physiological role of An HSD under natural pH is also discussed in A. nicotinovorans . Collectively, these findings provide a novel insight for a better understanding of a novel HSD, and a possible biotransformation method for preparing l -Asa.